2008
DOI: 10.1038/onc.2008.105
|View full text |Cite
|
Sign up to set email alerts
|

FLASH acts as a co-activator of the transcription factor c-Myb and localizes to active RNA polymerase II foci

Abstract: The c-Myb oncoprotein is a DNA-binding transcription factor with a key role in early stages of hematopoiesis. To expand our knowledge of partners cooperating with c-Myb, we performed a yeast two-hybrid screening with full-length c-Myb as bait. Here, we report FLICEassociated huge protein (FLASH)/CASP8AP2 as a novel Myb-interacting protein. We show that FLASH interacts with the DNA-binding domain of c-Myb and enhances c-Myb-dependent reporter activity and expression of endogenous c-Myb target genes. Chromatin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…22 Shortly thereafter, Cajal bodies and HLBs were shown to be distinct structures also in mammalian cells. 23,24 Although Coilin is sometimes observed at HLBs in both Drosophila and mammalian cells, 16,[25][26][27] HLBs that do not contain Coilin are frequently observed. Moreover, genetic experiments show that HLB assembly occurs normally in the absence of Coilin.…”
mentioning
confidence: 99%
“…22 Shortly thereafter, Cajal bodies and HLBs were shown to be distinct structures also in mammalian cells. 23,24 Although Coilin is sometimes observed at HLBs in both Drosophila and mammalian cells, 16,[25][26][27] HLBs that do not contain Coilin are frequently observed. Moreover, genetic experiments show that HLB assembly occurs normally in the absence of Coilin.…”
mentioning
confidence: 99%
“…Moreover, the transcriptional regulatory activity of Myb is crucial for its transforming ability (Gonda et al, 1989;Lane et al, 1990;Hu et al, 1991). Multiple co-factors like p300/CBP, Mi-2a, FLASH and menin/MLL engage in the regulation of the transactivational activity of c-Myb (Dai et al, 1996;Oelgeschlager et al, 1996;Kasper et al, 2002;Saether et al, 2007;Alm-Kristiansen et al, 2008;Jin et al, 2010). Recently, the importance of coactivation by p300 in myeloid transformation was highlighted using a novel murine hematopoietic cell line transformation assay (Pattabiraman et al, 2009).…”
mentioning
confidence: 99%
“…Structural studies confirmed interaction between the TAD of c-Myb and the KIX domain of CBP (39), whereas disruption of this interaction by mutation perturbs hematopoiesis in vivo (5). Recent reports have also identified two novel coactivators, Mi-2α and FLASH, which interact with Myb through its DBD and NRD (40,41). c-Myb also interacts with the corepressors mSin3a, c-Ski, N-CoR, and Tif-1β through the NRD and the R2 and R3 repeats of the DBD (Fig.…”
Section: Introductionmentioning
confidence: 99%